2020
DOI: 10.1097/md.0000000000020515
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of high-viscosity cement in percutaneous vertebroplasty for treatment of Osteoporotic vertebral compression fractures

Abstract: To evaluate the efficacy and safety of high viscosity bone cement in the percutaneous vertebroplasty (PVP) for treatment of single-level osteoporotic vertebral compression fractures. Eighty patients were enrolled in this study. All patients were received PVP, and they were divided into 2 groups according to the viscosity of bone cement, either high viscosity bone cement (HV group) or low viscosity cement (LV group). Oswestry Disability Index questionnaire and visual analog scale as clinical assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Contrary to the former study, three papers reported the different results. F G et al [13]observed the clinical e cacy of high or low viscosity bone cement in 200 OVCF cases the same as Li K et al [15]observed in 80 cases and Miao F et al [16]. observed in 178 cases.…”
Section: Bone Cement Related Factorsmentioning
confidence: 55%
See 2 more Smart Citations
“…Contrary to the former study, three papers reported the different results. F G et al [13]observed the clinical e cacy of high or low viscosity bone cement in 200 OVCF cases the same as Li K et al [15]observed in 80 cases and Miao F et al [16]. observed in 178 cases.…”
Section: Bone Cement Related Factorsmentioning
confidence: 55%
“…High-viscosity bone cement can reduce leakage, but whether it has relationship with pain relief rarely reported in the past. In the recent years, 4 four prospective studies [13][14][15][16] and one metaanalysis [17]on viscosity that maybe deal with our question were published. The level evaluation of the ve articles indicated the evidence is relatively high.…”
Section: Bone Cement Related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published study involving 130 patients, who underwent percutaneous vertebral augmentation, all patients received 2-to 6-mL cement injections per vertebra during the procedure, and PMMA leakage to the vena cava was found in two cases and to the intervertebral disc was found in eight patients [10]. In another recent study comparing high-viscosity bone cement and low-viscosity bone cement, in which PVP was performed in a total of 80 patients with single-level OVCF, no statistically significant difference was observed in terms of VAS and ODI scores whereas high-viscosity bone cement was reported to cause less PMMA leakage [11]. In the present study, the absence of serious bone cement leakage in both groups may be attributed to the fact that high-viscosity PMMA, which is more effective and safer, has been preferred.…”
Section: Discussionmentioning
confidence: 93%
“…Scholars tend to divide bone cement into 2 different types, high-viscosity bone cement and low-viscosity bone cement, and then analyze their clinical efficacy and safety. [14][15][16][17] Guo et al 18 pointed out that compared with low-viscosity bone cement, highviscosity bone cement had no difference in clinical efficacy and had a lower cement leakage rate. Ran Lador et al 19 found out that PVP with high viscosity bone cement resulted in less chance of leakage to endplates and vessels.…”
Section: Discussionmentioning
confidence: 99%